Analisis Tingkat Kebisingan Menggunakan Model Calculated of Road Traffic Noise di Area UPN “Veteran” Jawa Timur - Dinayah, Ignacia Putri; Rachmanto, Tuhu Agung (Jurnal Serambi Engineering, 2025)
Each year, universities enroll new students, which increases the use of motorized vehicles. An increase in the number of motorized vehicle users can cause noise impacts around the learning area, which can disrupt the learning process. The data needed is vehicle volume, vehicle speed, and road specifications. The collected data are then processed using the CoRTN model to obtain the noise level. The research was conducted at UPN "Veteran" East Java with 4 locations in the morning, afternoon and evening. Based on the results obtained, the peak of vehicle volume occurred in the afternoon with 14,763 vehicles at point 1, the highest vehicle speed occurred at 12.30 WIB at points 1 and 2 with 15 Km/hour, the highest noise occurred in the afternoon at point 2, namely 84 dB(A), and the noise with the lowest intensity occurred in the afternoon at point 4 with 62 dB(A). The noise level prediction results indicate that the noise exceeds the quality standard. Noise is affected by vehicle volume and vehicle speed. However, the vehicle volume affects the vehicle speed. The larger roads but low volume, vehicle speed will increase. However, if the volume is high, the vehicle speed will decrease. The statistics show that the model is good enough to explain the influence of vehicle volume and vehicle speed on noise.